2016
DOI: 10.1016/j.icarus.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Spectral variability on primitive asteroids of the Themis and Beagle families: Space weathering effects or parent body heterogeneity?

Abstract: Themis is an old and statistically robust asteroid family populating the outer main belt, and resulting from a catastrophic collision that took place 2.5±1.0 Gyr ago. Within the old Themis family a young sub-family, Beagle, formed less than 10 Myr ago, has been identified. We present the results of a spectroscopic survey in the visible and near infrared range of 22 Themis and 8 Beagle families members. The Themis members investigated exhibit a wide range of spectral behaviors, including asteroids with blue/neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 73 publications
0
33
1
Order By: Relevance
“…The low-albedo X-complex asteroids could be compositionally similar to those of the C-complex (DeMeo et al 2009(DeMeo et al , 2015. An indication of the composition similarities and origin between the low-albedo asteroids belonging to the X-and C-complex also comes from the fact that C-and X-complex asteroids have been found within the same families (Morate et al 2016;Fornasier et al 2016). In the near-infrared survey of Popescu et al (2018) asteroids belonging to the Xcomplex are denoted by the class Xt.…”
Section: Characteristics Of the Spectroscopic X-complexmentioning
confidence: 99%
“…The low-albedo X-complex asteroids could be compositionally similar to those of the C-complex (DeMeo et al 2009(DeMeo et al , 2015. An indication of the composition similarities and origin between the low-albedo asteroids belonging to the X-and C-complex also comes from the fact that C-and X-complex asteroids have been found within the same families (Morate et al 2016;Fornasier et al 2016). In the near-infrared survey of Popescu et al (2018) asteroids belonging to the Xcomplex are denoted by the class Xt.…”
Section: Characteristics Of the Spectroscopic X-complexmentioning
confidence: 99%
“…Initial studies of primitive asteroid families with different ages, such as the Themis, Beagle, and Veritas families, show spectral differences. However, the cause for these differences between families is not clear; SpWe may not be necessary to explain these spectral differences, but it cannot be ruled out (Nesvorný et al 2005;Ziffer et al 2011;Campins et al 2012;Fornasier et al 2016).…”
Section: Effects Of Space Weathering On Spectral Observations Of Primmentioning
confidence: 99%
“…Significant contributions are also expected in the understanding of asteroids families; for example, spectra of main belt asteroids as small as 2 km in diameter will constrain or determine the composition and thermal evolution of a family's parent body. In the case of the Themis family, one of the largest and oldest primitive families, Gaia's spectra will also help establish the role of water and hydrated minerals in the puzzling nature of the ''activated asteroids'' (also known as main belt comets) within this family (Fornasier et al 2016;Campins et al 2012).…”
Section: The Visible Regionmentioning
confidence: 99%
“…Meanwhile, spectroscopic observations of samples of both Beagle and Themis family asteroids showed that Beagle family asteroids are spectrally bluer, have higher albedos, and exhibit smaller spectral slope variability than background Themis family asteroids, suggesting that the Beagle parent body could have been a particularly blue and bright interior fragment of the original Themis parent body (Fornasier et al 2016).…”
Section: The Themis and Beagle Familiesmentioning
confidence: 99%